2017
DOI: 10.1158/1541-7786.mcr-16-0286-t
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotyping and Transcriptomic Outcomes in PDX-Derived TNBC Tissue

Abstract: Cancer tissue functions as an ecosystem of a diverse set of cells that interact in a complex tumor microenvironment. Genomic tools applied to biopsies in bulk fail to account for this tumor heterogeneity, whereas single-cell imaging methods limit the number of cells which can be assessed or are very resource intensive. The current study presents methods based on flow cytometric analysis and cell sorting using known cell surface markers (CXCR4/CD184, CD24, THY1/CD90) to identify and interrogate distinct groups … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The tumor microenvironment is complex, and clinically relevant information on tissue context, including cell–cell interactions, or in situ variations are lost in in vitro studies based on single cell suspensions or tumor cell lines. This critical lack of knowledge is a major obstacle to our understanding of how malignant cells interact with or manipulate the functions of non-malignant surrounding tissue or immune cells, and to the successful development of novel therapies, including immunotherapies ( 128 ). However, tumor environments, especially for solid tumors, can largely be preserved in patient-derived xenograft (PDX) models ( 129 ).…”
Section: Translational Models Of Cancer: Patient-derived Xenograftsmentioning
confidence: 99%
“…The tumor microenvironment is complex, and clinically relevant information on tissue context, including cell–cell interactions, or in situ variations are lost in in vitro studies based on single cell suspensions or tumor cell lines. This critical lack of knowledge is a major obstacle to our understanding of how malignant cells interact with or manipulate the functions of non-malignant surrounding tissue or immune cells, and to the successful development of novel therapies, including immunotherapies ( 128 ). However, tumor environments, especially for solid tumors, can largely be preserved in patient-derived xenograft (PDX) models ( 129 ).…”
Section: Translational Models Of Cancer: Patient-derived Xenograftsmentioning
confidence: 99%
“…Single-cell studies preserve information that is lost in bulk tumor gene expression assays, which cannot compartmentalize data by cell type and thus are unable to distinguish changes in expression that arise from gene regulation versus shifts in the cellular composition of a mixed sample. Immunophenotyping has recently shown promise as one approach for addressing this issue and assessing heterogeneity in bulk tumor biopsies (66) Assessing subclonal architecture using cell-free ctDNA. The CAPP-Seq technique leverages novel bioinformatics methods and library construction techniques optimized for low amounts of input DNA (58).…”
Section: Single-cell Analysis Of Bulk Tumor Tissuementioning
confidence: 99%
“…A recent study on the stemness of cancer cells confirmed that during the passage of PDX mouse model, the stemness of cancer cells is gradually shaped by the murine microenvironment [ 62 ]; this finding indicates that the expression of MUC1 can be altered in this progress. Similarly, another gene involved in the stemness maintenance of cancer cells, PROM1 [ 55 , 63 ], can also have differential expression patterns.…”
Section: Discussionmentioning
confidence: 99%